Antimicrobial and antioxidant properties of Morchella spp. Collected from Udhampur district of J&K - Boomika Gupta; Dr. Upma Dutta; Chaudhary, Aarushi; Gupta, Sachin; Bandral, Julie D; Mahajan, Tanika; Vasundra; Kour, Aarshdeep; Kour, Sneahpreet (Mushroom Research, 2025)
Morchella have long been known for their medicinal properties. In J&K, Morchella locally known as “guchhi” are found in the forests and are being utilized in the healthcare industry as medicinal mushroom because it has a wide range of pharmacological activities and anti- inflammatory effects. In the present study, the fruiting bodies of Morchella spp. were collected from five regions of districtUdhampur of J&K and tissue culture of the five isolates were designated i.e., Isolate-101, Isolate- 102, Isolate-103, Isolate-104 and Isolate-105. Results of preliminary investigation against human pathogens by disc diffusion method revealed that Isolate-102 showed best inhibition against human pathogens (Pseudomonas aeruginosa, Salmonella typhi and Klebsiella pneumonia). Secondarymetabolite of fruiting bodies and mycelium of potential Isolate-102 was extracted using ethanol and ethyl acetate. The crude extracts of mycelium and fruiting bodies were further studied for antimicrobial and antioxidant activities. The results of antimicrobial study showed that the mycelium inhibited Pseudomonas aeruginosa and Salmonella typhi (4.41mm and 11.16mm) whereas fruiting bodies didn’t show any inhibition. The antioxidant activity (DPPH method and Carotene/Linoleic acid test) showed more inhibition (IC50) in mycelium whereas the phenolic and flavonoid content was higher in fruiting bodies. The investigation showed that the Morchella mushroom mycelium is an excellent source of antioxidants and capable of imparting protection at different levels.